PERKEMBANGAN PENYELENGGARAAN LELANG NON EKSEKUSI OLEH PEJABAT LELANG KELAS 2 (NOTARIS) DIMASA PANDEMI COVID -19 - Fransiscus Liono, Cliff Edward; Malombeke, Erick; Thariqi, Muhammad Rayhan; Daba Dida, Dewi F.M. (Universitas Ekasakti, 2023)
Notaries are included in the Class II. Unlike Class I Auction Officers who can conduct various types of auctions, Class II Auction Officers are only authorized to handle Voluntary Non-executory Auctions. Voluntary Non-Execution Auction is an auction to carry out the sale of goods owned by individuals, groups of individuals or private business entities that are auctioned voluntarily by their owners. This paper is prepared using the normative juridical method, which will discuss the development of auction rules, especially during the Covid-10 Pandemic. With the existence of PMK No.213/PMK.06/2020 concerning Instructions for Auction Implementation, Notaries including Class II Auction Officials can implement the new provisions. Some examples of problems that have the potential to hinder the implementation of auctions by notaries as Class II Auction Officials include a provision where each Auction participant must deposit an Auction bid guarantee of at least 20% and a maximum of 50% of the auction limit value must pay the auction price and Auction Duty which is carried out no later than five working days after the implementation of the Auction. This certainly makes it difficult for the Covid-19 Pandemic condition because people's purchasing power is declining. In addition, the potential for holding auctions electronically can be disrupted by some cyber notary obstacles.